Quantitative B-lymphocyte deficiency and increased TCRγδ T-lymphocytes in acute infectious spondylodiscitis. Issue 1 (December 2018) - Haugaard, Anna; Marquart, Hanne; Kolte, Lilian; Ryder, Lars; Kehrer, Michala; Krogstrup, Maria; Dragsted, Ulrik; Dahl, Benny; Gjørup, Ida; Andersen, Åse; Garred, Peter; Nielsen, Susanne
Abstract Acute infectious spondylodiscitis (AIS) is a serious infection of the spine with rising incidence and a mortality of 3–6%. The role of the immune system in AIS is largely unknown. We performed extensive B and T-lymphocyte phenotyping in patients with AIS at diagnosis and after treatment cessation. In this prospective multicentre study, flow cytometric analysis of T and B-lymphocyte subsets was performed in 35 patients at diagnosis and 3 months after treatment cessation. We additionally analysed levels of immunoglobulins and IgG subclasses, serum level and genetic variants of mannose-binding lectin, and somatic hypermutation. A total of 22 (61%) patients had B-lymphocytes below reference limit at baseline, persisting in 7 (30%) patients at follow-up. We found a lower proportion of CD19 + CD27 + IgD+ marginal zone B-lymphocytes and a higher proportion of γδ+ T-lymphocyte receptors compared with controls at both time points. Immunoglobulin levels were elevated at baseline compared to follow-up, and not associated with absolute B-lymphocyte count. In conclusion, a large proportion of AIS patients presented with profound B-lymphocyte deficiency, only partly reversible at follow-up. Identification of immune dysfunction related to AIS may allow for future targeted therapeutic interventions to restore host immunity.